The effect of ultrasound-guided sciatic nerve - Huang, Zhi; Cai, Yan; Yang, Yunfei; Shi, Jin; Zhao, Xuya; Mp, Haise; Zeng, Qingfan (Journal of Medical Biochemistry, 2022)
Objective: To investigate the effects of different anesthesia methods on the levels of inflammatory and coagulation factors in the peripheral blood of elderly patients undergoing hip surgery. Methods: 144 elderly patients undergoing hip arthroplasty in our hospital were randomly divided into ultrasound-guided lumbar-sciatic nerve block (group A) and epidural anesthesia (group B), 72 cases in each group. The postoperative hemodynamic indexes, pain score, inflammatory factors and coagulation factor levels were compared between the two groups. Results: (1) The postoperative VAS score of group B patients was lower than that of group A (P<0.05); (2) The SBP and DBP of group B were higher than those of group A at T1 and T2. (both P<0.05); (3) Compared with group A, the levels of IL-6, IL-8 and TNF-α in the peripheral blood of patients in group B decreased at postoperative T2, T3 and T4 (P<0.05); (4) Compared with group A, plasma FV:C, FVIII:C and FIB in group B decreased, and TT increased during surgery after T2, T3 and T4, (all P<0.05). Conclusion: Compared with epidural anesthesia, lumbar-sciatic nerve block can reduce the levels of peripheral blood coagulation factors and inflammatory factors after surgery.